Seeds that give revisited: Participatory plant breeding and rural revitilization - Song, Yiching; Vernooy, Ronnie (China Agriculture Press, 2023)
In 2003, the International Development Research Centre (IDRC) of Canada published “Seed that give. Participatory plant breeding,” synthesizing the achievements and lessons learned of the first 10 (pioneering) years of participatory plant breeding (PPB), a concept first tabled at an international workshop in Wageningen, the Netherlands, in 1994. IDRC was one of the early and most fervent supporters of PPB. See: https://publications.gc.ca/site/eng/9.648982/publication.html In “Seeds that give revisited,” the PPB champions highlighted in the 2003 book present and reflect on their work over the last 20 years, joined by a group of Chinese professionals who were inspired by the early PPB work, bringing the approach to new regions and crops. Contributors write about significant results obtained, but also about (new) challenges. The Conclusion brings the cases together.